Mechanism of Lower Airway Hyperresponsiveness Induced by Allergic Rhinitis - Yiting Liu; Jichao Sha; Cuida Meng; Dongdong Zhu (Journal of Immunology Research)
Allergic rhinitis is a global illness that puzzles many researchers. Most patients with allergic rhinitis also have lower airway hyperresponsiveness, and an allergic rhinitis attack can increase lower airway hyperresponsiveness. However, the mechanism of the effect of allergic rhinitis on the lower airways is still unclear. In this paper, the effects of allergic rhinitis on the lower airways are studied in terms of epidemiology, anatomy, pathophysiology, nasal function loss, inflammation drainage, nasobronchial reflex, and whole-body circulatory flow to determine the mechanism involved and provide ideas for future diagnosis, treatment, and experiments.